Study of cutaneous manifestations of polycystic ovarian syndrome - Kaur, Sukhleen; Gupta, Sunil K.; Juneja, Sunil K.; Kaur, Sukhjot; Rani, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Polycystic ovarian syndrome (PCOS) is one of the most frequently encountered endocrine disorders that occurs in as many as 4 to 10% of women of reproductive age group. It presents with a series of skin changes including acne, hirsutism, seborrhea, androgenetic alopecia (AGA) and acanthosis nigricans. Aim of the study was to determine the prevalence and frequency of different cutaneous manifestations in PCOS patients and to correlate them with the degree of hormonal abnormalities. Methods: A total 100 patients with features of PCOS who presented to department of dermatology, gynecology (January 2018-December 2019) with cutaneous manifestations were recorded and diagnosis of PCOS was made using Rotterdam’s criteria. Pregnant women and diagnosed cases of any other endocrine disorder were excluded. Hirsutism was assessed using Ferriman-Gallwey score and AGA according to Ludwig’s classification. Serum hormonal profile including FSH, LH, prolactin, testosterone (free), DHEAS, TSH, FBS, fasting insulin were done. Insulin resistance was determined by calculating HOMA-IR score. Results: Among cutaneous manifestations of PCOS, hirsutism (85%) was the most common finding followed by acne (73%), seborrhea (50%), AGA (36%), acanthosis nigricans (29%) and acrochordons (9%). The most common hormonal abnormality was insulin resistance in 53% patients, followed by raised free testosterone in 19% and serum prolactin in 18% patients. A statistically significant association was present between AGA and insulin resistance, hirsutism and raised prolactin levels, seborrhea and raised body mass index (p < 0.05). Conclusions: Dermatological manifestations of PCOS play a significant role in making the diagnosis and constitute a substantial portion of the symptoms experienced by women with this syndrome.